The Effect of Toxic Organic Chemicals on Mogan Lake - Karaaslan, Y.; Akkoyunlu, A.; Erturk, F.; Citil, E. (SPRINGER INTERNATIONAL PUBLISHING AG, 2013)
In this study, the effect of some toxic organic chemicals on Mogan Lake has been investigated using the AQUATOX Model. The unique property of the Model includes the sub ecotoxicological model when compared to the other water quality models. The ecosystem model AQUATOX, which is one of the few general ecological risk models that represents the combined environmental repercussions and effects of toxic organic chemicals, was selected for this study. The Model also supplies conventional pollutants, such as nutrients and sediments, and considers several trophic levels, including attached and planktonic algae, submerged aquatic vegetation, several types of invertebrates, and several types of fish. All data measured at both lake and creeks have been loaded into the AQUATOX Model as both initial concentration and dynamic loading for the year of 2002. Then, the AQUATOX Model was calibrated and verified for the years of 2004 and 2005. After verification and calibration, the effects of toxic organic substances such as Dieldrin, Simazin, Carbofuran, PCB 180, Malathion, Tefluthrin, PCB 101, Fluridone, Pentachloropenol, DDT, Parathion, EPTC, PCB 110, Chlordane and Alochlor, all of which are found in the AQUATOX Library, on phytoplanktons and zooplanktons in the Mogan Lake, have been observed for one year. The results have indicated that zooplanktons are more sensitive to specific toxic substances than phytoplanktons. It has been seen that phytoplanktons have grown through getting toxic substances at first, and then tended to decrease after a definite time. However, some zooplankton species maintained their growth by taking toxic organic substances.
Keywords: Simulation; Dangerous Substances; Toxicity; Modeling; the AQUATOX Model; WATER-QUALITY; AQUATOX; Environmental Sciences & Ecology